(untitled) (World Economics and Finance Bulletin, 2024)
This paper explains the definition of production and its importance for the economy. It elaborates the essence of production in Islamic economy and the meaning of the verses about production. The principles of production in Islamic economics are explained through examples. It is shown their importance in ensuring economic and social well-being, environmental protection, and effective use of resources.